2022
DOI: 10.4103/ijo.ijo_2363_21
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic ophthalmia: A comprehensive update

Abstract: Sympathetic ophthalmia is a rare, bilateral, granulomatous, panuveitis following penetrating trauma or surgery to one eye. Clinical presentation commonly occurs within the first year of trauma occurrence but can be delayed by several years. It manifests as acute/chronic granulomatous uveitis with yellowish-white choroidal lesions or Dalen–Fuchs nodules. Initially, patients respond rapidly to corticosteroid therapy, but a majority require long-term use of corticosteroid-sparing agents to prevent recurrences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Specifically, vitrectomy is the technique most associated with SO, 7 with an incidence ranging from 0.01% to 1%. 8 The risk to develop SO after SB is considered to be significantly lower if compared to vitrectomy as intraocular structures remain relatively isolated from the conjunctiva if no external drainage manoeuvres are performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, vitrectomy is the technique most associated with SO, 7 with an incidence ranging from 0.01% to 1%. 8 The risk to develop SO after SB is considered to be significantly lower if compared to vitrectomy as intraocular structures remain relatively isolated from the conjunctiva if no external drainage manoeuvres are performed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple surgeries have been linked to an increased risk of developing the disease. 8 Prompt administration of immunomodulatory therapy is crucial to achieve anatomical resolution of SO and to prevent potentially irreversible vision loss. In this regard, Tan et al found good visual outcomes in a cohort of SO patients treated with early systemic and regional corticosteroid therapy, followed by long-term stepwise use of immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was once debatable whether evisceration is contraindicated in penetrating ocular injury due to the potential risk of sympathetic ophthalmia 29 . Sympathetic ophthalmia is a bilateral simultaneous granulomatous panuveitis due to the exposure of immune-privileged ocular antigens from an exciting eye following penetrating ocular trauma or surgery 30 . Activation of the immune response was once attributed to residual uveal tissue after evisceration 31,32 .…”
Section: Indications Of Eviscerationmentioning
confidence: 99%
“…29 Sympathetic ophthalmia is a bilateral simultaneous granulomatous panuveitis due to the exposure of immune-privileged ocular antigens from an exciting eye following penetrating ocular trauma or surgery. 30 Activation of the immune response was once attributed to residual uveal tissue after evisceration. 31,32 However, sympathetic ophthalmia has been proven to be associated with genetic factors.…”
Section: Indications Of Eviscerationmentioning
confidence: 99%